Freelancing and digital nomadism : satisfaction and well-being of entrepreneurs - Zhang, Yuqi; Dvouletý, Ondřej; Andera, Michal, 1984-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
This thesis investigates the well-being and work-life balance of freelancers and digital nomads, a subgroup of independent workers which is experiencing increasing popularity. Using a quantitative approach with a survey (N=106) carried out from March to April 2025, the study explored how industry segment (creative vs. technical/business), job autonomy, income stability, job satisfaction and work-life balance strategies influence well-being, with boundary management practices posing as an additional research question. The survey was designed based on applicable theoretical frameworks. Data was collected online via relevant community groups and analyzed using Structural Equation Modeling, regression and group comparison tests, while thematic coding was used for open-ended responses. The findings reveal that industry segment significantly predicts well-being in the sample population, with creative professionals reporting lower well-being scores and greater financial instability. Job satisfaction emerged as the strongest positive predictor of well-being. While job autonomy and a composite work-life balance score did not show significant direct links to well-being in multivariate models, open-ended responses of the sample highlighted the importance of personalized strategies, mindset and social connections. The thesis concludes that well-being in independent work is shaped by a complex interaction of structural factors, such as industry and financial stability. Personal strategies and internal perspectives seem to play a key role in boundary management in the sample population. Moreover, the findings suggest that autonomy alone is insufficient to guarantee well-being without conscious management and personal fulfillment.
Vedoucí práce: Ondřej Dvouletý
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses